The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fpls.2015.00956
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous target mimics down-regulate miR160 mediation of ARF10, -16, and -17 cleavage during somatic embryogenesis in Dimocarpus longan Lour

Abstract: MicroRNA160 plays a critical role in plant development by negatively regulating the auxin response factors ARF10, -16, and -17. However, the ways in which miR160 expression is regulated at the transcriptional level, and how miR160 interacts with its targets during plant embryo development, remain unknown. Here, we studied the regulatory relationships among endogenous target mimics (eTMs), and miR160 and its targets, and their involvement in hormone signaling and somatic embryogenesis (SE) in Dimocarpus longan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 52 publications
(90 reference statements)
3
44
0
Order By: Relevance
“…The auxin-related miRNAs frequently target the fundamental components of the auxin signaling pathway, including the ARFs, which are involved in SE induction [27,93]. Accordingly, insights into embryogenic cultures of Arabidopsis and other plants indicated that miR160 could directly regulate the expression of ARF10, ARF16, and ARF17; miR167 seems to the control expression of ARF6 and ARF8, while miR390 possibly downregulates the ARF2, ARF3, ARF4 transcripts [55,63,64,68,81,85,86].…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…The auxin-related miRNAs frequently target the fundamental components of the auxin signaling pathway, including the ARFs, which are involved in SE induction [27,93]. Accordingly, insights into embryogenic cultures of Arabidopsis and other plants indicated that miR160 could directly regulate the expression of ARF10, ARF16, and ARF17; miR167 seems to the control expression of ARF6 and ARF8, while miR390 possibly downregulates the ARF2, ARF3, ARF4 transcripts [55,63,64,68,81,85,86].…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…ARF4 and AUX22B genes were selected from the plant hormone signal transduction pathway, which are the two key transcription factors involved in regulating the expression of auxin-responsive genes. Auxin response factor (ARFs) is considered as essential SE genes that are specifically activated during embryogenic differentiation [31][32][33][34]. ARFs bind auxin response promoter elements, mediate transcriptional responses to auxin and regulate auxin-mediated transcriptional activation/repression, together with Aux/IAA [35,36].…”
Section: Candidate Gene Expression Pattern Validationmentioning
confidence: 99%
“…Similar to the widely documented involvement of miRNA molecules in plant development in vivo (Jin et al, 2013), the expression of miRNAs was reported during in vitro induced SE in several plant species including Citrus sinensis, Dimocarpus longan, Gossypium hirsutum, Larix kaempferi, Larix leptolepis, Liriodendron tulipifera × L. chinense, Manihot esculenta , and Zea mays (Zhang et al, 2012, 2014; Li et al, 2013; Lin and Lai, 2013; Yang et al, 2013; Chávez-Hernández et al, 2015; Wu et al, 2015; Lin et al, 2015a,b; Khatabi et al, 2016). Thus, the engagement of miRNAs in the embryogenic transition that is induced in vitro is assumed, although knowledge about the function of the specific miRNA in SE induction is very limited.…”
Section: Introductionmentioning
confidence: 99%